2018
DOI: 10.1038/gim.2017.241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical whole-genome sequencing from routine formalin-fixed, paraffin-embedded specimens: pilot study for the 100,000 Genomes Project

Abstract: on behalf of the 100,000 Genomes Project Purpose: Fresh-frozen (FF) tissue is the optimal source of DNA for whole-genome sequencing (WGS) of cancer patients. However, it is not always available, limiting the widespread application of WGS in clinical practice. We explored the viability of using formalin-fixed, paraffin-embedded (FFPE) tissues, available routinely for cancer patients, as a source of DNA for clinical WGS. Methods:We conducted a prospective study using DNAs from matched FF, FFPE, and peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 39 publications
3
117
0
Order By: Relevance
“…Our comparison of mutational rates in primary vs persistent/recurrent LSCC needs to be interpreted in this light. However, several recent studies have demonstrated high (ie, > 90%) concordance rates in detection of SNVs and CNVs in coding genomic regions between matched fresh‐frozen and FFPE tumor samples . In addition, comparison of amplicon‐based, targeted exome sequencing to TCGA dataset is a well‐established practice in the HNSCC literature .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our comparison of mutational rates in primary vs persistent/recurrent LSCC needs to be interpreted in this light. However, several recent studies have demonstrated high (ie, > 90%) concordance rates in detection of SNVs and CNVs in coding genomic regions between matched fresh‐frozen and FFPE tumor samples . In addition, comparison of amplicon‐based, targeted exome sequencing to TCGA dataset is a well‐established practice in the HNSCC literature .…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have demonstrated high (ie, > 90%) concordance rates in detection of SNVs and CNVs in coding genomic regions between matched freshfrozen and FFPE tumor samples. [28][29][30] In addition, comparison of amplicon-based, targeted exome sequencing to TCGA dataset is a well-established practice in the HNSCC literature. 11,13 Thus, we believe that these differences in DNA sequencing methodology do not significantly diminish the validity of our comparisons and conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite optimization of DNA extraction methods, formalin-fixation induces DNA artefacts that increase the false positive mutation rate 22 . We therefore applied a stringent variant allele frequency (VAF) filter (see Methods) on all FFPE-derived data, and chose a genomic region unlikely to be affected by RS driver mutations (i.e.…”
Section: Mutation Burdenmentioning
confidence: 99%
“…Paraffin was removed from FFPE 10μm sections scraped from 5-10 slides using the Adaptive Focused Acoustics (AFA™) on the M220 Focused-ultrasonicator. DNA was thereafter purified with the truXTRAC FFPE DNA Kit according to the manufacturer's protocol (Covaris Inc., Woburn, MA, USA), but using optimized reverse cross-linking conditions as previously described 22 . Peripheral blood samples were subjected to a ficoll gradient centrifugation to isolate mononuclear cells.…”
Section: Chop-or Cohortmentioning
confidence: 99%
“…At 2-4x coverage, WGS provides thousands of read pairs per 100kb segment, a substantive amount enough to enable sensitive CNA detection. This provides an improved resolution compared to SNP microarrays in which there are approximately 60 probes per 100kb segment.Identifying copy number variation with high coverage WGS data have been studied extensively in basic and clinical research settings[29][30][31] . For example, in a recent systematic benchmark, Trost et al reported good performance of using >20x WGS data for identifying small-scale CNVs (1 -100kb)32 .…”
mentioning
confidence: 99%